Soluble CD137 is a novel serum marker of liver cirrhosis in patients with hepatitis C and alcohol‐associated disease etiology. Issue 4 (26th December 2021) - Weigand, Kilian; Peschel, Georg; Grimm, Jonathan; Luu, Khang; Schacherer, Doris; Wiest, Reiner; Müller, Martina; Schwarz, Herbert; Buechler, Christa
Abstract: Defective T‐cell functions play a role in the persistence of HCV infection. Activated T cells express CD137, which costimulates antivirus T‐cell responses, and this activity is antagonized by soluble CD137 (sCD137). Here, we show that in sera of 81 patients with chronic HCV, sCD137 levels did not correlate with measures of viral infection, and did not decline after virus eradication using direct‐acting antivirals. Thus, serum sCD137 was similar in patients infected with HCV and in uninfected controls. Of note, in HCV patients with liver cirrhosis and patients with mostly alcohol‐associated liver cirrhosis, sCD137 was increased. A negative association of sCD137 and albumin existed in both cohorts. sCD137 concentrations were similar in hepatic and portal vein blood excluding the liver as the origin of higher levels. Recombinant sCD137 reduced Th1 and Th2 but not Th17 cell polarization in vitro, and accordingly lowered IFN‐γ, TNF, and IL‐13 in cell media. Serum sCD137 is associated with inflammatory states, and positively correlated with serum TNF in cirrhotic HCV patients following virus eradication. Our study argues against a role of sCD137 in HCV infection and suggests a function of sCD137 in liver cirrhosis, which yet has to be defined. Abstract : Soluble CD137 (sCD137) regulates T‐cell functions, which are disturbed in HCV infection. Serum levels of sCD137 are similar in healthy controls, HCV‐infected patients, patients with sustained virological response (SVR) after therapy with direct‐acting antivirals and patients with alcohol abuse. sCD137 is induced in patients with liver cirrhosis.